Cinema digital e educação: novas formas de percepção estética no século XXI - Siqueira, Paula Monteiro (2015)
The art goes through transformations on elapse of time, as do the resources and techniques used to produce it, and it s transformed as well as the predominant medium of communication alleged experience mediation. At the beginning of the 20th century Benjamin identified this process and analysed its effects, particularly through movies (BENJAMIN, 1987) and nowadays, with digital movie development, we observe several transformations which impact movie s language and the ways that spectators interact with it. Under the hypothesis that techniques applied to digital movies modify the way that spectators interact with the film, we develop our research on defining a cutout on stereoscopy, which produces the depth effect on 3D movies, and the use of CGI (computer generated imagery), which consists in computer created and animated images, having the target to discuss the impact of these resources on spectator s experience of interaction with movies, and more specifically to investigate new features of digital cinema aiming to understand what are the possible changes on movie s language and broached contents, as well as recognizing features of the ways of perception that might come up on this circumstances. For these purposes we develop a theoretical and empirical research grounded on the theoretical references of Critical Theory of Society.